Rola wczesnej edukacji i opieki w ograniczaniu skutków ubóstwa wśród dzieci - Elżbieta Subocz (Problemy Wczesnej Edukacji)
This article attempts to answer the question: what role does the process of early childhood education and care play in reducing the effects of poverty among children? The main argument of the article states that education (started as early and lasting as long as possible) is the only chance to limit the negative consequences of poverty, as well as to overcome the intergenerational transmission of poverty and social exclusion. Relying on the results of foreign (mostly American) surveys, it has been proven that good quality early childhood education and care is beneficial for children living in poverty, as well as for society as a whole. It positively influences the social and emotional development of children, their language skills and school achievements. Children who benefited from institutions / programmes for early childhood education and care, in adulthood do better in the labour market, have higher earnings and are less likely to seek stimulants. Society bears lower costs of special education, anti-social behaviour, criminal proceedings, social welfare and health of young people and adults.